HLA Population Genetics in Solid Organ Transplantation. Issue 9 (September 2017) - Kransdorf, Evan P.; Pando, Marcelo J.; Gragert, Loren; Kaplan, Bruce
Abstract : Abstract: HLAs are fundamental to the adaptive immune response and play critical roles in the cellular and humoral response in solid organ transplantation. The genes encoding HLA proteins are the most polymorphic within the human genome, with thousands of different allelic variants known within the population. Application of the principles of population genetics to the HLA genes has resulted in the development of a numeric metric, the calculated panel-reactive antibody (CPRA) that predicts the likelihood of a positive crossmatch as a function of a transplant candidate's unacceptable HLA antigens. The CPRA is an indispensible measure of access to transplantation for sensitized candidates and is used as the official measure of sensitization for allocation of points in the US Kidney Allocation System and Eurotransplant. Here, we review HLA population genetics and detail the mathematical basis of the CPRA. An understanding of these principles by transplant clinicians will lay the foundation for continued innovation in the care of sensitized patients. Abstract : Kransdorf and colleagues review HLA population genetics and the mathematical basis used to derive the calculated panel reactive antibody (CPRA). CPRA is a basic component of variables used for organ distribution. Understanding these principles is critical for effective organ allocation. Supplemental digital content is available in the text.